THE INFLUENCE OF LEADERSHIP STYLE, ORGANIZATIONAL CULTURE AND CAREER DEVELOPMENT ON JOB SATISFACTION THROUGH WORK MOTIVATION AS AN INTERVENING VARIABLE IN ACEH PROVINCE CENTER FOR STATISTICS - Sari Yunus; Adnan; Heriyana (RADJA PUBLIKA, 2023)
This study aims to examine the effect of leadership style, organizational culture and career development on job satisfaction with work motivation as a mediating variable for District/City BPS employees in Aceh Province. The number of respondents in this study were 214 civil servants at the Regency/City BPS in Aceh using the Stratified Random Sampling method. The data analysis method used is Structural Equation Modeling with AMOS Software. The results of this study found that leadership style and organizational culture directly had a significant effect on job satisfaction, while career development had no significant effect on work motivation. Then work motivation has a significant effect on job satisfaction, while leadership style, organizational culture and career development have no significant effect on job satisfaction. The results of the mediation effect prove that work motivation is able to mediate the effect of leadership style and organizational culture on job satisfaction partially (partial mediation), but is unable to mediate the effect of career development on job satisfaction.